AB0999 TREATMENT FOLLOW UP AFTER TRANSITION FROM PAEDIATRIC TO ADULT RHEUMATOLOGY CARE. (June 2019) - Koren, Brigita; Tomazin, Maja; Berce, Vojko; Pahor, Artur; Holc, Iztok
Abstract : Background: Many juvenile onset rheumatic diseases continue to have activity in adulthood. Therefore, a continuous uninterrupted healthcare of these patients is needed. Objectives: To determine whether and how therapy has changed in patients after transition from paediatric to adult rheumatology service in our medical centre. Methods: A retrospective single centre study was performed. Patients seen at least once at both paediatric and adult rheumatology outpatient service were enrolled. Data was collected from patients medical records. Results: A total of 50 patients were included. Most of them were female (82%). Average age at transition was 19, 6 years (range 18- 27 years). Mean time of follow up was 44 months (range 2- 119 months). Juvenile idiopathic arthritis (JIA) was the most common juvenile onset chronic rheumatic disease. The medications used either as monotherapy or in combination before transition at last visit at paediatric rheumatology outpatient unit were nonsteroidal anti-inflammatory drugs (NSAIDs) (14%), corticosteroids (6%), synthetic disease modifying antirheumatic drugs (DMARDs) (18%), biologic DMARDs (2%). After transition 34% of patients used NSAIDs, 16% corticosteroids, 24% synthetic DMARDs, 8% biologic DMARDs. Without any medication before and after transition were 66% and 48% of patients, respectively. After transition 36% of patients had their therapy changed. 30% needed escalation of therapy because their disease was still active or they experienced exacerbation. Most changes in therapy occurred in the first year after transition. Conclusion: We confirmed that many patients with juvenile onset rheumatic disease had changes in their therapy after transition, especially escalations of therapy. Most changes occurred in the first year after transition which is a vulnerable period in a young adult life. References: [1] Foster H, et al. EULAR/PReS standards and recommendations for the transitional care of young people with juvenile- onset rheumatic diseases. Ann Rheum Dis2017;76:639-46. [2] Jensen PT, et al. Quantitative evaluation of a pediatric rheumatology transition program. Pediatric Rheumatology 2015; 13:17. [3] Kanakoudi-Tsakalidou F. The art of transitioning pediatric patients with rheumatic diseases to adult rheumatologists. Mediterr J Rheumatol 2016;27(2):55-8. [4] Luque Ramos A. Transition to adult rheumatology care is necessary to maintain DMARD therapy in young people with juvenile idiopathic arthritis. Semin Arthritis Rheum2017;47(2):269-75. Disclosure of Interests: None declared